PELAKSANAAN KOORDINASI ANTARA PEMERINTAH PROVINSI RIAU DENGAN STAKEHOLDER DALAM MENANGGULANGI KEBAKARAN HUTAN DAN LAHAN DI PROVINSI RIAU TAHUN 2019 - Maiyur Ningsih; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
n 2019, forest and land fires occurred in Riau Province according to data from the Sipongi - Karhutla Monitoring System as many as 90,550.00 hectares of burned land area. Forest and land fires do not only occur once, but occur every year in Riau Province, this indicates that the Riau Provincial Government and stakeholders have not succeeded in controlling forest and land fires. The purpose of this study is to determine the implementation of coordination between the Riau Provincial Government and Stakeholders in tackling forest and land fires in Riau Province in 2019 and to determine the factors that hinder coordination in tackling forest and land fires in Riau Province in 2019. This study uses an approach qualitative with descriptive method. In collecting data, the author uses interview and documentation techniques. The results of this study are . to tackle forest and land fires in Riau Province The coordination carried out by the BPBD of Riau Province with stakeholders has not fully worked out, the lack of cooperation and the slow pace of prevention has caused forest and land fires to still occur. The inhibiting factor in the implementation of coordination between the Riau Provincial Government and Stakeholders in tackling forest and land fires in Riau Province in 2019 were internal and external constraints. Internal constraints in the form of lack of communication are still the lack of cooperation due to lack of preparation such as planning to prevent forest and land fires from occurring, while external obstacles include: preparedness constraints such as limited tools and lack of public knowledge. Keywords: Implementation of Coordination, Combating Karhutla